The Association Between Health Literacy and Quality of Life and Its Associated Factors Among Adults with Type 2 Diabetes Mellitus in Public Primary Care Clinic / Nur Amirah Shibraumalisi ... [et al.] - Shibraumalisi, Nur Amirah; Mat Nasir, Nafiza; Md Yasin, Mazapuspavina; Isa, Mohamad Rodi (Universiti Teknologi MARA Cawangan Selangor, 2020)
Introduction: Low health literacy (HL) is one of the contributing factors that leads to negative diabetic outcome. Quality of life (QOL) is a state of complete physical, mental and social well- being. There is limited evidence on association of HL and QOL among type 2 diabetes mellitus (T2DM), therefore the objectives of this study were to identify the HL and QOL status, to determine the association between HL and QOL and factors associated with QOL among T2DM patients. Methods: This was a cross sectional study involving patients with T2DM from two public primary care clinics. HL and QOL were measured using translated and validated HLS – Asia Q16 and DQoL-BCI questionnaires respectively among T2DM patients. Results: The mean HL score was 12.39 (3.34), 17.7 % had “inadequate HL”, 25.7% had “problematic HL” and 56.6% had “sufficient HL”. The mean DQoL-BCI score was 32.09 (6.51). Lower QOL level was negatively associated with age (b -0.140; CI: -0.190, - 0.090; p<0.001), not obese (b -1.476; CI: -2.605, - 0.347; p<0.011), and HL level (b -0.425; CI: -0.59, - 0.259; p<0.001). Lower QOL level was positively associated with uncontrolled glycaemic status (HbA1c >6.5%) (b 1.308; CI: -0.042, 2.659; p<0.058), treatment with insulin (b 4.163; CI:1.538, 6.788; p<0.002) and combination treatment of insulin and oral hypoglycaemic agents (OHA) (b 2.450; CI:1.145, 3.756; p<0.001). Conclusions: This study demonstrated that age, body mass index, HL, glycaemic control, treatment with OHA and insulin were significantly associated with QOL. This suggest the importance of identifying high risk patients with poor QOL for targeted intervention.